Dynamic Marketing Capabilities and Sustainable Marketing Performance: The Mediating Role of Sustainable Market Innovation Ambidexterity in the Tourism Industry - Riyoko, Sisno; Ali, Ali; Naili, Naili (Universitas Muhammadiyah Yogyakarta, 2026)
Tourism destinations face increasing pressure to achieve marketing performance that is both competitive and environmentally and socially sustainable. Although dynamic marketing capabilities (DMC) are widely recognized as crucial for adapting to market changes, empirical evidence on how these capabilities translate into sustainable marketing performance remains limited. Grounded in dynamic capability theory and ambidexterity logic, this study investigates the mediating role of sustainable market innovation ambidexterity (SMIA) in the relationship between DMC and sustainable marketing performance in the tourism industry. A quantitative research design was applied using survey data collection from 250 tourism enterprises, including hotels, travel agencies, tourism villages, and tourist attractions in Central Java, Indonesia. Structural equation modeling was employed to examine both direct and indirect relationships. The findings reveal that DMC has a significant positive effect on sustainable marketing performance, both directly and indirectly through SMIA. Furthermore, balancing sustainable market innovation ambidexterity emerges as a critical mechanism through which dynamic marketing capabilities are transformed into superior and sustainable marketing outcomes. This study contributes to tourism marketing literature by integrating dynamic marketing capabilities with sustainable market innovation ambidexterity, thereby extending capability-based performance frameworks. Managerially, the results offer strategic insights for tourism practitioners to develop adaptive and sustainability-oriented marketing strategies in dynamic environments.